Financial Distress Analysis Using Altman Z-Score, Springate and Zmijewski in Retail Companies on the IDX - Barnard Jacob; Han Huazheng; Huang Congzhao (Yayasan Adra Karima Hubbi, 2023)
Islamic Social Reporting (ISR) is an index of social accountability disclosure whose indicators refer to Islamic ethical principles. Islamic banking operates by sharia principles. Therefore the disclosure of ISR in Islamic banking must be within the corridors of Islamic theology. This study uses the E-Views software to identify the factors that influence the level of exposure to Islamic Social Reporting (ISR) in Islamic banking in Indonesia. The factors examined in this study are company performance and company size towards Islamic Social Reporting. The results of this study show that financial performance proxied by ROA has no effect on ISR with a calculated T value of 1.338357, and financial performance proxied by NPF has no impact on Islamic Social Reporting with an estimated T value of 1.405019. Company size is a proxy for the Size that affects Islamic Social Reporting, with a T-test result of 3.077773 <2.03693. The results of the F test obtained a value of 0.021230 <0.05, which means that the variables NPF, ROA, and Size together influence the Islamic Social Reporting of Islamic Banks in Indonesia for the 2016-2020 period.